Clinical neuroscience for communication disorders : neuroanatomy and neurophysiology - Blake, Margaret Lehman; Hoepner, Jerry K. (San Diego, CA : Plural Publishing, Inc., 2023)
'Clinical Neuroscience for Communication Disorders: Neuroanatomy and Neurophysiology offers a comprehensive and easy-to-understand introduction to neuroscience for undergraduates and beginning graduate students in the field of communication disorders. Packed with features to aid student understanding, this textbook introduces the neurologic underpinnings of systems involved in communication (speech, language, cognition, hearing) and swallowing. A highly readable writing style makes abstract and complex material accessible to students and provides just the right amount of information to challenge yet not overwhelm students'--
Overview of the nervous system -- Ventricular system : cranium, ventricles, and meninges -- Neuron anatomy and physiology -- Neuroembryology -- Diencephalon -- Somatosensory systems -- Visual system -- Auditory and vestibular systems -- Chemical senses : smell and taste -- Motor systems -- Cranial nerves -- Limbic system and reticular formation -- Cerebrovascular system -- Communication and cognition -- Neuroplasticity -- Clinical cases.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Communication Disorders; Nervous System Physiological Phenomena; Nervous System -- anatomy & histology; Neurosciences